474 Vulvar reconstruction in patients with advanced malignancies. (4th December 2020) - Bubliieva, Olha; Kostiuchenko, Yevgeniy; Motuziuk, Igor; Svintsitskiy, Valentyn; Nespryadko, Sergiy; Tsip, Nataly; Sydorchuk, Oleg; Samokhvalova, Alena
Abstract : Introduction/Background: Vulvar malignant tumors are the rarest oncological disease of women's reproductive system in Ukraine. In 2018 there were registered only 477 new cases of vulvar cancer among all Ukrainian women. It is approximately three cases per 100 thousand among female population. However there are less common histological types, such as leiomyosarcoma, melanoma and lymphangiosarcoma, which make up approximately 1% of all cases. The main goal in surgical treatment is to obtain gross surgical margins, which sometimes require the usage of reconstructive techniques. Methodology: Results: We presented two types of vulvar reconstructions at the time of primary treatment, using different types of flaps: medial thigh flap and rectus abdominal muscle flap. The histological types of tumors were vulvar squamous cell carcinoma and lymphangiosarcoma. The operation time was 320 and 420 minutes, the blood loss – 200 ml and 350 ml, the length of hospitalization was 12 and 14 days respectively. Both of patients suffered pain before surgery, and were relived after. There were no postoperative complications. None of patients had flap loss. Conclusion: The use of skin flap for reconstruction in treatment of advanced vulvar cancer can improve functional status. It is associated with the low rate of postoperative complications and decreasing pain, which significantly better the women's quality of life. Disclosures: Authors declare no disclosures.